What Drives Eco-Friendly Toy Purchases? The Mediating Role of Consumer Attitude - Andina Fasha; Golan Hasan; Vebbie Kavitan; Shafie Mohamed Zabri (Yayasan Sinergi Kawula Muda, 2026)
This study investigates consumers’ purchase intention toward eco-friendly toys in Batam, Indonesia. In this context, product safety and environmental considerations intersect in parental decision-making yet remain underexplored in green marketing research. Drawing on the Stimulus–Organism–Response (SOR) framework, the study examines how key external stimuli shape internal evaluations and subsequent behavioral intentions. A quantitative cross-sectional survey was conducted with 499 parents who had purchased or considered purchasing toys for their children, and the data were analyzed using PLS-SEM. The findings reveal that consumer attitude plays a central mediating role, translating external cues into purchase intention, with health-related considerations emerging as the most influential driver of attitudes relative to other factors. This highlights the distinctiveness of eco-friendly toys as a product category in which perceived safety and health benefits outweigh purely environmental motives. The study contributes theoretically by extending the SOR framework into a child-related consumption context in an emerging market, demonstrating that attitudinal formation is primarily anchored in protective and trust-based evaluations. Empirically, the results underscore that, in Batam, purchase intention toward eco-friendly toys is driven more by health-oriented concerns than by environmental considerations alone, offering a more context-specific understanding of green consumer behaviour.